OUTCOMES OF MODIFIED RADICAL MASTECTOMY MRM VS BREAST CONSERVATION SURGERY BCS. : JPUMHS;2024:14:03,20- 25.http://doi.org/10.46536/jpumhs/2024/14.03.530 - Saadia Muhammad1, Hikmat Ullah Qureshi2, Muhammad Bilawal Khan3, Ali Gohar Khan4, Sarwat Noreen5 , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: Breast cancer is the most common malignancy in women and leads to substantial health issues globally. Historically, Modified Radical Mastectomy (MRM) total removal of breast and tissue was a standard treatment of choice. However, advances in surgical techniques as well as oncological care has led way for Breast Conservation Surgery (BCS), where the tumor is removed, while preserving the breast's appearance. While the intent of both approaches is to provide an adequate oncological control, the perioperative outcomes, complication rates and the resulting patient quality of life have been a matter of ongoing debate when discussing comparative efficacy and aesthetic outcome. Objective: To compare the outcome of two different surgical methods, Modified Radical Mastectomy (MRM) and Breast Conservation Surgery (BCS), in treatment of breast cancer. MATERIALS And Methods: This comparative observational study was carried out at General Surgery Department Hayatabad Medical Complex Peshawar during the period (August 2020 to October 2021). A total of 120 female patients suffering from breast cancer were enrolled. A total of 57(47.5%) patients underwent MRM(Group A) whereas 63(52.5%) further received BCS for tumor excision while maintaining breast appearance (Group B). RESULTS: Axillary lymph node metastasis was present in 19(33.3%) cases in group A and 22(34.9%) cases in group B. In group A there were 34(59.6%) cases of TNM stage-1 and 23(40.4%) cases had stage-II, while in group B stage-I was noted in 41(65%) cases and stage-II in 22(35%) cases respectively. In group A invasive ductal carcinoma was observed in 42(73.6%) cases, invasive lobular carcinoma in 10(21.3%) and other types were 5(8.8%), while on the other hand in group B these figures were 46(73%), 12(19%) and 5(7.9%) respectively. There was no significant difference in age, menopause status and other general data, suggesting that the two groups were comparable (P>0.05). CONCLUSION: BCs provides better perioperative outcomes, lesser postoperative complications and aesthetic superiority than MRM in breast cancer patients.